ECOOP 2009 -- Object-Oriented Programming 23rd European Conference, Genoa, Italy, July 6-10, 2009, Proceedings - Drossopoulou, Sophia (Programming and Software Engineering, 2009)
This book constitutes the refereed proceedings of the 23rd European Conference on Object-Oriented Programming, ECOOP 2009, held in Genoa, Italy, in July 2009. The 25 revised full papers, presented together with the abstracts of 2 invited talks and the ECOOP 2008 banquet speech were carefully reviewed and selected from a total of 117 submissions. The papers cover topics such as types, frameworks and modeling; aliasing and transactions; access control and verification; modularity; mining and extracting; refactoring; concurrency, exceptions and initialization; and concurrency and distribution.